Synthesis, Characterization, Spectral Studies And Antimicrobial Activity Of 2-[1-(2-Hydroxy-Phenyl)-Ethylidene Amino]-4-Methylphenol With Complexes Of Cd (II) And Hg (II) Ions - SURAJ B. ADE,; M.N. DESHPANDE,; D.G. KOLHATKAR, (International Journal of Pharma and Bio Sciences, 2012)
Transition metal (II) complexes of the type ML1 [where M=Cd(II) and Hg(II), L1=Schiff base derived from 2-amino, 4-methyl phenol and O-hydroxy acetophenone] have been prepared, characterized by elemental analysis, molar conductivity, IR, electronic spectra, NMR spectral and X-ray diffraction studies. Molar conductivity measurements indicate that the complexes are non-electrolyte in nature. The analytical data confirm metal to ligand ratio in the complexes were 1:1. IR spectral data suggests that the ligand (AMPOHA) behaves as tridentate ONO donar system. X-ray diffraction studies determine monoclinic crystal system for these complexes. The Schiff base and their metal complexes have been tested for their antibacterial and antifungal activity using disc diffusion methods.